2002
DOI: 10.1212/01.wnl.0000036908.39696.fd
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in attention

Abstract: The profile of attentional impairments and fluctuating attention is similar in PD dementia and DLB with parkinsonism. The current findings do not support the current arbitrary distinctions between these patient groups. Importantly, patients with PD do not experience fluctuating attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
166
0
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(184 citation statements)
references
References 51 publications
12
166
0
6
Order By: Relevance
“…Attention and vigilance is similar to Lewy body dementia and shows a fluctuating course. Reaction time is increased and attention to new signals is decreased (7).…”
Section: Introductionmentioning
confidence: 99%
“…Attention and vigilance is similar to Lewy body dementia and shows a fluctuating course. Reaction time is increased and attention to new signals is decreased (7).…”
Section: Introductionmentioning
confidence: 99%
“…CAF is a neuropsychological test [6] able to evidence, on the basis of patient and caregivers interviews, the presence of fluctuating consciousness. The questionnaires are able to discriminate 85% of DLB patients, as confirmed by autopsy [7]. Cognitive fluctuations are considered a clinical feature typical of DLB, described in 70-80% of these patients, only in 14-20% of AD patients and in 15-30% of VaD subjects [8].…”
Section: Synucleinopathies: Dementia With Lewy Bodiesmentioning
confidence: 81%
“…Although also described in other forms of dementia, visuospatial impairment is more severe in PDD patients (Huber et al, 1989), and it has been suggested that impaired performance in visuospatial tasks may be related to problems with sequential organization of behavior, thus expressing a frontal executive dysfunction rather than pure parieto-occipital pathology (Stern et al, 1983). Attention is compromised with presence of attentive fluctuations (Ballard et al, 2002). Psychotic symptoms are frequently associated with dementia in PD, with a prevalence ranging between 25 and 30% (Ravina et al, 2007).…”
Section: Dementiamentioning
confidence: 99%
“…The investigators reported an improvement of 2.1 scores in the MMSE compared to the placebo group (p=0.013), with no change in the UPDRS scores at the end of the study. However, although this trial suggested that donepezil can improve cognition in patients with PD without worsening of motor function, the study results are limited by the small sample size and by the crossover design, as no washout period was allowed between the two stages of the trial (Aarsland et al, 2002). The second study involved 16 patients randomized to receive donepezil 2.5-10 mg or placebo for 18 weeks.…”
Section: Donepezilmentioning
confidence: 99%